Integrating Fractional Sines

Calculus Level 4

π 6 π 6 sin 2 x sin 3 x d x = ? \large \int_{-\frac \pi 6}^\frac \pi 6 \frac {\sin 2x}{\sin 3x} dx = ?


The answer is 0.76035.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Aug 26, 2018

I = π 6 π 6 sin 2 x sin 3 x d x sin 2 x sin 3 x is an even function. = 2 0 π 6 sin 2 x sin 3 x d x = 2 0 π 6 2 sin x cos x 3 sin x 4 sin 3 x d x Let u = sin x d u = cos x d x = 4 0 1 2 u 3 u 4 u 3 d u = 4 3 0 1 2 1 1 4 3 u 2 d u Let sin θ = 2 3 u cos θ d θ = 2 3 d u = 2 3 0 sin 1 1 3 sec θ d θ = 2 3 ln ( tan θ + sec θ ) 0 sin 1 1 3 = 2 3 ( ln ( 1 2 + 3 2 ) ln ( 0 + 1 ) ) = 1 3 ln ( 1 + 3 2 ) 2 = ln ( 2 + 3 ) 3 0.760 \begin{aligned} I & = \int_{-\frac \pi 6}^\frac \pi 6 \frac {\sin 2x}{\sin 3x} dx & \small \color{#3D99F6} \frac {\sin 2x}{\sin 3x} \text{ is an even function.} \\ & = 2 \int_0^\frac \pi 6 \frac {\sin 2x}{\sin 3x} dx \\ & = 2 \int_0^\frac \pi 6 \frac {2\sin x\cos x}{3\sin x - 4\sin^3 x} dx & \small \color{#3D99F6} \text{Let }u = \sin x \implies du = \cos x\ dx \\ & = 4 \int_0^\frac 12 \frac u{3u - 4u^3} du \\ & = \frac 43 \int_0^\frac 12 \frac 1{1 - \frac 43 u^2} du & \small \color{#3D99F6} \text{Let }\sin \theta = \frac 2{\sqrt 3}u \implies \cos \theta\ d\theta = \frac 2{\sqrt 3}\ du \\ & = \frac 2{\sqrt 3} \int_0^{\sin^{-1}\frac 1{\sqrt 3}} \sec \theta \ d\theta \\ & = \frac 2{\sqrt 3} \ln(\tan \theta + \sec \theta) \bigg|_0^{\sin^{-1}\frac 1{\sqrt 3}} \\ & = \frac 2{\sqrt 3} \left(\ln\left(\frac 1{\sqrt 2} + \sqrt{\frac 32}\right)- \ln (0+1) \right) \\ & = \frac 1{\sqrt 3}\ln \left(\frac {1+\sqrt 3}{\sqrt 2}\right)^2 \\ & = \frac {\ln \left(2+\sqrt 3\right)}{\sqrt 3} \\ & \approx \boxed{0.760} \end{aligned}

Donglin Loo
Aug 25, 2018

π 6 π 6 s i n 2 x s i n 3 x d x \displaystyle\int_{-\cfrac{\pi}{6}}^{\cfrac{\pi}{6}} \cfrac{sin2x}{sin3x} dx

Let f ( x ) = s i n 2 x s i n 3 x f(x)=\cfrac{sin2x}{sin3x}

f ( x ) = s i n ( 2 x ) s i n ( 3 x ) = s i n 2 x s i n 3 x = s i n 2 x s i n 3 x = f ( x ) f(-x)=\cfrac{sin(-2x)}{sin(-3x)}=\cfrac{-sin2x}{-sin3x}=\cfrac{sin2x}{sin3x}=f(x)

f ( x ) = s i n 2 x s i n 3 x f(x)=\cfrac{sin2x}{sin3x} is even function.

π 6 π 6 s i n 2 x s i n 3 x d x = 2 0 π 6 s i n 2 x s i n 3 x d x = 2 0 π 6 2 s i n x c o s x 3 s i n x 4 s i n 3 x d x = 2 0 π 6 2 c o s x 3 4 s i n 2 x d x = 4 0 π 6 c o s x 3 4 s i n 2 x d x \therefore \displaystyle\int_{-\cfrac{\pi}{6}}^{\cfrac{\pi}{6}} \cfrac{sin2x}{sin3x}dx=2\displaystyle\int_{0}^{\cfrac{\pi}{6}} \cfrac{sin2x}{sin3x}dx=2\displaystyle\int_{0}^{\cfrac{\pi}{6}} \cfrac{2sinxcosx}{3sinx-4sin^3x}dx=2\displaystyle\int_{0}^{\cfrac{\pi}{6}} \cfrac{2cosx}{3-4sin^2x}dx=4\displaystyle\int_{0}^{\cfrac{\pi}{6}} \cfrac{cosx}{3-4sin^2x}dx

Let y = s i n x d y = d ( s i n x ) = c o s x d x y=sinx\Rightarrow dy=d(sinx)=cosxdx

When x = π 6 , y = s i n π 6 = 1 2 x=\cfrac{\pi}{6}, y=sin\cfrac{\pi}{6}=\cfrac{1}{2}

When x = 0 , y = s i n 0 = 0 x=0, y=sin0=0

π 6 π 6 s i n 2 x s i n 3 x d x = 4 0 1 2 1 3 4 y 2 d y = 4 0 1 2 1 ( 3 + 2 y ) ( 3 2 y ) d y = 4 2 3 0 1 2 ( 1 3 + 2 y + 1 3 2 y ) d y \displaystyle\int_{-\cfrac{\pi}{6}}^{\cfrac{\pi}{6}} \cfrac{sin2x}{sin3x}dx=4\displaystyle\int_{0}^{\cfrac{1}{2}} \cfrac{1}{3-4y^2}dy=4\displaystyle\int_{0}^{\cfrac{1}{2}} \cfrac{1}{(\sqrt{3}+2y)(\sqrt{3}-2y)}dy=\cfrac{4}{2\sqrt{3}}\displaystyle\int_{0}^{\cfrac{1}{2}} (\cfrac{1}{\sqrt{3}+2y}+\cfrac{1}{\sqrt{3}-2y})dy

= 2 3 [ l n ( 3 + 2 y ) 2 + l n ( 3 2 y ) 2 ] 0 1 2 = 1 3 [ l n ( 3 + 2 y ) l n ( 3 2 y ) ] 0 1 2 = 1 3 [ l n 3 + 2 y 3 2 y ] 0 1 2 =\cfrac{2}{\sqrt{3}}[\cfrac{ln(\sqrt{3}+2y)}{2}+\cfrac{ln(\sqrt{3}-2y)}{-2}]_{0}^{\cfrac{1}{2}}=\cfrac{1}{\sqrt{3}}[ln(\sqrt{3}+2y)-ln(\sqrt{3}-2y)]_{0}^{\cfrac{1}{2}}=\cfrac{1}{\sqrt{3}}[ln\cfrac{\sqrt{3}+2y}{\sqrt{3}-2y}]_{0}^{\cfrac{1}{2}}

= 1 3 ( l n 3 + 1 3 1 l n 3 3 ) = 1 3 ( l n 3 + 1 3 1 l n 1 ) = 1 3 ( l n 3 + 1 3 1 0 ) 0.76035 =\cfrac{1}{\sqrt{3}}(ln\cfrac{\sqrt{3}+1}{\sqrt{3}-1}-ln\cfrac{\sqrt{3}}{\sqrt{3}})=\cfrac{1}{\sqrt{3}}(ln\cfrac{\sqrt{3}+1}{\sqrt{3}-1}-ln1)=\cfrac{1}{\sqrt{3}}(ln\cfrac{\sqrt{3}+1}{\sqrt{3}-1}-0)\approx0.76035

Just like \frac you should do for \sin \ln for example sin x s i n x sin x the sin and x are in italic and no space between them. But \sin x sin x \sin x , sin is not in italic because it is a function and not a constant or valuable. x is in italic because it is a variable. Also note that there is a space between sin and x. All function, such as \cos, \tan, \sum, \int must have a \ similarly, \alpha α \alpha , \beta β \beta ...

Just use \frac for the limit will do the \cfrac making it too big. You don't need braces {} for example \int_0^\frac \pi 6 0 π 6 \int_0^\frac \pi 6 . You only need braces when the operand is more than one character for example. \frac 1{23}, \frac {23}3

Chew-Seong Cheong - 2 years, 9 months ago

Log in to reply

Thanks for the info, sir!

donglin loo - 2 years, 9 months ago

Log in to reply

Where do you live? I am in Petaling Jaya.

Chew-Seong Cheong - 2 years, 9 months ago

Log in to reply

@Chew-Seong Cheong I live in Kuala Lumpur, somewhere around the Kepong district. But I'm now studying overseas.

donglin loo - 2 years, 9 months ago

Log in to reply

@Donglin Loo Studying in Australia? You can add me on Facebook if you want ChewSeong Cheong .

Chew-Seong Cheong - 2 years, 9 months ago

Log in to reply

@Chew-Seong Cheong Ok sure, I will add you sir. Mine is Donglin Loo, pls look out. BTW, I am not studying in Australia, I am studying in Singapore instead.

donglin loo - 2 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...